Mechanical properties of denture base resins: An evaluation - Pooran Chand; Chandra Bhusan Singh Patel; Balendra Pratap Singh; Raghuwar Dayal Singh; Kamleshwar Singh (Wolters Kluwer Medknow Publications, 2011)
Background: Acrylic resin dentures are susceptible to fracture after clinical use, which is a problem of concern in prosthodontics. Impact failure outside the mouth and flexure fatigue failure in the mouth are two most important causes of fracture of denture base. Aim: This study evaluated the transverse deflection and transverse strength of four commercial brands of heat cure acrylic resin (Stellon, Acrylin-H, Trevalon and Trevalon-HI). Materials and Methods: An experimental design was adapted. Twenty-four rectangular strip specimens, six for each group, were prepared. Strips were finished on the edges and equally from the both the molded surfaces to make strips of specific dimensions. The tests were conducted mainly in accordance with the American Dental Association Specification no. 12/ISO: 1567-1981 (ISO: 6887-1986) for denture base polymer. The transverse deflection and transverse strength were measured by Instron testing machine. Intergroup differences were assessed using student "t" test. Results: The heat cure denture base material D (Trevalon "HI") had the minimum mean value of transverse deflection under different loads. Trevalon "HI" also had minimum value of mean transverse strength among different brands of acrylic resins. There was no statistically significant variation between Stellon, Acrylin-H and Trevalon, but variation was significantly higher with D (Trevalon "HI") vs. Stellon, Acrylin-H and Trevalon. Conclusion: The heat cure denture base material D (Trevalon "HI") was the strongest and C (Trevalon) was the weakest among all materials used in this study. The study showed that the deflection of various denture base resins (A to D) increases proportionately with the increase in load.